2012
DOI: 10.1016/j.indmarman.2012.01.013
|View full text |Cite
|
Sign up to set email alerts
|

The contrary forces of innovation

Abstract: In this paper, we argue that industrial innovation processes can productively be analyzed as consisting of two sub-processes that over time create and mobilize contrary forces within both internal and external interactions of the innovation project. One of these forces emerges from the process of mobilizing resources, activities, and actors in ensuring commitments to the project over time. The other is the process of explorative learning, which continues to create revised or even new propositions about the rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…Data has been collected through three main sources: direct semistructured interviews and participating observation conducted by one of the coauthors (Hoholm and Olsen, 2012) as primary sources, and company's websites, sectorial magazines and editorials, press briefings and corporate reports as secondary sources.…”
Section: Methodsmentioning
confidence: 99%
“…Data has been collected through three main sources: direct semistructured interviews and participating observation conducted by one of the coauthors (Hoholm and Olsen, 2012) as primary sources, and company's websites, sectorial magazines and editorials, press briefings and corporate reports as secondary sources.…”
Section: Methodsmentioning
confidence: 99%
“…Some other studies (e.g., Baraldi, et al, 2001;Fonseca, 2001;Håkansson and Waluszewski, 2002;Nerkar and Shane, 2003;Waluszewski, 2004;Baraldi and Strömsten, 2006;Hoholm and Olsen, 2012;Alexis, 2014) indicated that a possible source of uncertainty is the resources' own conflicting properties. Resources (for example, raw materials, machinery, knowledge) are heterogeneous (Penrose, 1959).…”
Section: Sources Of Uncertainties In the Innovation Processmentioning
confidence: 99%
“…3. Resources are not always available either due to focal actors' inability to produce them, unwillingness of other actors to exchange necessary resources, by any institutional restriction, by the unsuccessful combination of differential and conflicting resources from previously undertaken activities (Goldratt, 1997;Fonseca, 2001;Gadde and Håkansson, 2001;Spencer, 2003;Håkansson and Walusewski, 2002;Waluszewski, 2004;Chaturvedi, et al, 2009;Hoholm and Olsen, 2012;Muller, 2013;Petruzzelli and Savino, 2014). Due to resource unavailability the linking of activities may become uncertain and eventually a condition called inertia can appear in the activity sequence (Goldratt, 1997).…”
Section: Theoretical Modelmentioning
confidence: 99%
“…It “creates tension between a resource exposed to a force and the history of the resources it has interfaces with” (Håkansson and Waluszewski, 2002a, p. 225). Friction generated through tensions in resource interfaces transforms existing resource combinations or creates new ones; therefore, it is a transformational force (Hoholm and Olsen, 2012). This also means that any force directed towards a resource will produce a reaction that will be distributed to all resources through resource interfaces.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…A particularly useful concept for analysing the disruptive process of digital transformation within RIA is friction, which describes any destabilising movement or force between resources linked to other interconnected resources (Håkansson and Waluszewski, 2002a). When introducing new technologies or digital processes within highly traditional analogue processes, friction between different resource types is bound to occur (Fremont et al, 2019;Hoholm and Olsen, 2012). This friction may be a source of both positive and negative outcomes in terms of co-created and codestroyed value (Håkansson and Waluszewski, 2002a).…”
Section: Introductionmentioning
confidence: 99%